Don`t wait for the beep - Gibson, N.; McCunn, R. (Sport Performance & Science Reports, 2019)
Fitness assessments are a well-established component of sport and education programmes for youth athletes, however, they traditionally involve exercise intensities and recovery periods that are externally controlled. Whilst this o ers a reliable and valid means of assessing tness, it removes the necessity, apparent in training and competition, for those taking part to self-regulate exercise intensity and recovery intermissions. Self-regulated assessments of physical capacity may o er a useful means of addressing this gap. Data from self-regulated repeated sprint assessments in youth soccer, discussed herein, have highlighted some interesting ndings regarding running performance and maturation. At present, more work is required to understand whether a similar approach would work for the assessment of aerobic capacity and the performance of high intensity intermittent running. With sports searching for new and improved methods of identifying and selecting talent, this may represent an attractive proposition, providing researchers, coaches and practitioners invest time in understanding the reliability of such protocols and generating new knowledge around how the resultant data should be interpreted. Whether we are ready to do away with the eponymous `beep' remains to be seen.